Valutazione dello sforzo percepito e risposte del lattato ematico durante uno "special judo fitness test" in judoisti iraniani titolati e non titolati - Arazi, H.; Heidari, N. (Medicina dello Sport, 2013)
The aim of this study was to verify the potential differences in performance, acute blood lactate responses and rating of perceived exertion (RPE) between elite and non-elite judokas based on SJFT. Methods. Eighteen judokas (mean±standard deviation: 22.67±2.14 years old, 177±4.64 cm of height, 73.6±9.9 kg of body mass and at least two years of regular judo training background) took voluntarily part in this study. Participants were classified into elite and non-elite from their rankings in different competitions; subjects performed SJFT after familiarization session. Rating of perceived exertion in three series and blood lactate (LA) before and 3 minutes after test were assessed. Statistical analysis was done using Student`s independent t-test, one-way ANOVA with repeated measures and correlation by Karl Pearson`s correlation coefficient. Results. Findings of this study demonstrated that elite`s heart rate one min after test was less than non-elite group (P=0.001), number of throws in second (P=0.014), third (P=0.001) and sum of three phases (P=0.002) in elite were more than non-elite judokas. Estimated fitness index was better for elite in comparison to non-elite group (P=0.001). RPE results showed a difference between group (P=0.01) in the second and third time. Conclusion. The results of this investigation showed that SJFT can be used as a valid test to discrimination fitted from unfitted judokas.